Preventing and developmental factors of sustainability in healthcare organisations from the perspective of decision makers: an exploratory factor analysis - Mario Calabrese; Shefqet Suparaku; Savino Santovito; Xhimi Hysa (BMC, 2023)
Abstract Background UN Sustainable Development Goals are part of the political agenda of most developed countries. Being a developing country, Albania has only recently adhered to this trend. Prior research at national level has sporadically focused on environmental sustainability, neglecting a holistic view of the phenomenon. To fill this gap, this study aims to explore preventing and developmental factors of sustainability in healthcare organisations from the perspective of decision makers by relying to a Triple Bottom Line approach. Methods Data were collected through a questionnaire administered to healthcare facilities and analysed through the Exploratory Factor Analysis. Findings revealed that the factors influencing the sustainability of the national healthcare system were five: Barriers of Organisational Sustainability; Stakeholders Pressure (regarding sustainable issues); Awareness (knowledge and measures taken for sustainability); Institutional Engagement; and Personal Interest and Involvement. The underlying factors included 19 items suitable for this sample, representing 64.371% of the total variance. Results The findings show the existence of 4 factors: Barriers of Organisational Sustainability, Stakeholders Pressure regarding Sustainable issues, Awareness/knowledge and measures taken for sustainability, Personal Interest and Involvement. Conclusions It is evident that national health organisations should continuously improve its strategies to be consistent with the sustainable development goals of international organisations, so that their initiatives could reflect the integration of sustainability approaches at the organisational level.